Scattering length monitoring at the SNO+ detector - Langrock, S; Lidgard, J; Turner, E; Segui, L; Reichold, A; Wilson, JR (IOP Publishing, 2017)
SNO+ is a neutrinoless double beta decay and low energy neutrino experiment located in Sudbury, Canada. To improve our understanding of the detector energy resolution and systematics, calibration systems have been developed to continuously monitor the optical properties of the detector, such as absorption, reemission and scattering. This poster provides an overview of the scattering calibration system: the Scattering Module of the Embedded LED/Laser Light Injection Entity (SMELLIE), designed to measure the scattering length in situ, over a wavelength range of 375nm - 700nm. We present analyses for both water and scintillator filled detector states.